Art of Atari - Lapetino, Tim (Dynamite Entertainment, 2016)
"ATARI is one of the most recognized names in the world. Since its formation in 1972, the company pioneered hundreds of iconic titles including Asteroids, Centipede and Missile Command. In addition to hundreds of games created for arcades, home video systems, and computers, original artwork was specially commissioned to enhance the Atari experience, further enticing children and adults to embrace and enjoy the new era of electronic entertainment. ART OF ATARI is the first official collection of such artwork. Sourced from museums and private collections worldwide, this book spans over 40 years of the company's unique illustrations used in packaging, advertisements, catalogs, and more!,"--Amazon.com.